Insider trading on the UK stock market: information contents and managerial incentives - Ajlouni, Moh'd Mahmoud (2004)
This study investigates the managerial incentive of insider trading. A research subject that has not been empirically examined in the UK yet. In doing so, this study merges two parallels but related tracks: The information contents of insider trading which is a Finance subject backed by the Efficient Market Hypothesis (EMH) and the managerial incentives of insider trading which is a Management subject backed by the Agency Theory. In fact, the managerial incentives of insider trading only becomes testable once there is evidence that insider trading is profitable.